Polish tax system overview - Jacek Wantoch-Rekowski; Martyna Wilmanowicz (Prawo Budżetowe Państwa i Samorządu)
The article analyses the “tax system” concept. The authors have mainly referred to the views of the Polish tax law doctrine. The analysis also covers issues on public levies, with a particular emphasis on taxes, their most important components. The article also presents issues concerning the classification of taxes and their structure.